Clinical spectrum of thrombocytopenia - A hospital based prospective study (Journal of Pathology of Nepal, 2024)
Background: Platelets play a vital role in coagulation. The normal platelet count ranges from 280+/-130 x 109/L. A reduction in platelet count below 150x109/L is defined as thrombocytopenia. The present study was carried out to evaluate the clinico-hematological profile of various patients with thrombocytopenia and to study age and gender-wise distribution, various etiological factors, severity of thrombocytopenia and its association with bleeding manifestations in patients.Materials and Methods: This prospective study was conducted at the hematology section of the department of Pathology at a tertiary care centre, Ahmedabad, Gujarat, India for a period of two years including 300 patients. EDTA samples were analyzed in5-part automated hematology analyzer. Thrombocytopenia cases were confirmed by peripheral blood smear examination.Results:  Thrombocytopenia was predominant in males (n=178, 59.3%). Most common age group was 20-29 years (n=81, 27%). Major clinical presentation was fever (n= 222, 74%) while bleeding manifestations were observed in only n=25, 8.3% patients. Association of thrombocytopenia with anemia was n=204, (68%) followed by leucopenia (n= 133, 44.3%) and pancytopenia (n=104, 34.6%). Bone marrow examination was done only in  40 (13.3%) patients. The majority had moderate thrombocytopenia (n=124, 41.3%) followed by mild (n=108, 36%). The most common etiology observed was COVID-19 (21%) followed by dengue (17%) and malaria (12.7%).Conclusions: Thrombocytopenia is a very commonly observed hematological entity. The clinical spectrum of thrombocytopenia is quite varied and ranges from infections to malignancies.